Combustion Characteristics Of Blends Of Kerosene And Cooking Oil At Various Fuel-Air Equivalence Ratio Simulation Approach - Kadir, Mohammad ‘Asri (Universiti Sains Malaysia, 2021)
A simulation has been conducted to evaluate the performance of a thermoelectric generator, with water-cooled heat exchanger. The simulation was conducted for three parts, which were the combustion of kerosene-vegetable cooking oil blend model, the temperature of cold side of TEG with water-cooled heat exchanger and the power generated by TEG. The plumbum telluride thermoelectrics module consists of 128 p-type and 128 n-type semiconductor legs. The model for combustion was conducted using five different blends of kerosene-vegetable cooking oil which were 100% Kerosene, 90% Kerosene, 75% Kerosene, 50% Kerosene and 25% Kerosene. Three different water flow rates of 0.005kg/s, 0.01kg/s and 0.03kg/s flow into the heat exchanger to simulate the temperature at the cold side of the thermoelectric generator. A maximum power ouput of 227 mW was achieved using 100% kerosene at 0aa.03 kg/s. The potential different ranged between 0.12V to 0.19V and the current ranged between 0.5A – 1.2 A.